2016
DOI: 10.29244/avi.3.2.45-50
|View full text |Cite
|
Sign up to set email alerts
|

Profil Kreatinin dan Nitrogen Urea Darah pada Anak Sapi Friesian Holstein yang Disuplementasi Zn

Abstract: Parameter kreatinin dan nitrogen urea darah atau blood urea nitrogen (BUN) dapat digunakan sebagai indikator untuk melihat adanya gangguan fungsi ginjal. Penelitian ini bertujuan untuk mengetahui kadar kreatinin dan BUN dalam serum anak sapi Friesian Holstein (FH) yang diberi suplementasi mineral Zn di dalam pakan. Penelitian ini menggunakan 9 ekor anak sapi FH yang sehat secara klinis dan umur berkisar antara 6-10 bulan. Hewan dibagi menjadi 3 kelompok, yaitu kelompok tanpa suplementasi Zn, kelompok yang dibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Higher than normal levels of BUN and creatinine indicate that there is a damage to kidney function. 24 Results showed that pups born to mothers that were provisioned with 2.5% Jamu ATOKE did not experience kidney damage. It can be seen that BUN and creatinine levels in ATOKE pups were not different compared to control.…”
Section: Discussionmentioning
confidence: 97%
“…Higher than normal levels of BUN and creatinine indicate that there is a damage to kidney function. 24 Results showed that pups born to mothers that were provisioned with 2.5% Jamu ATOKE did not experience kidney damage. It can be seen that BUN and creatinine levels in ATOKE pups were not different compared to control.…”
Section: Discussionmentioning
confidence: 97%
“…This compound is present a little in the plasma of adult animals, while in the plasma of animals that are growing there is more ( [16]). Adding the opinion of [17] stated that creatinine levels in the blood are more sensitive in detecting renal organ damage than BUN levels, because creatinine does not undergo reabsorption and is excreted through the kidney tubules.…”
Section: Creatinine Levelmentioning
confidence: 99%